KINERJA PRAMUSAJI TAMING SARI RESTAURANT DI TURI BEACH RESORT BATAM - Murni "; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Turi Beach Resort is located in Hang Lekiu street, Nongsa, Batam, KepulauanRiau. Turi Beach Resort is a part of Nongsa Resort. This is Resort is strategicplaceso it is being favorite for local and foreign tourist. The research aim is todetermine the waiter’s skill in Taming Sari Restaurant in Turi Beach ResortBatam. This research methodology was by using quantitative datas by descriptiveapproach to identify the problems in Taming Sari Restaurant. The respondent isfive person. The data collection technic is observation, interview, anddocumentation. The result shows that the waiter’s skill in Taming Sari Restauranfrom the quality is 80%, quantity is 75%, timing is 79%, dan team work is 82%.On the waiter’s skill is not based on the rules/SOP. It determine how good is thewaiter’s skill in Taming Sari Restaurant in Turi Beach Resort Batam.Keywords: Performance, waiter, Restaurant, Resort.